Ruling capital: Emerging markets and the reregulation of cross-border finance - Kevin Gallagher (Cornell University Press, 2014)
This book demonstrates how several emerging market and developing countries (EMDs) managed to reregulate cross-border financial flows in the wake of the global financial crisis, despite the political and economic difficulty of doing so at the national level. It also shows that some EMDs, particularly the BRICS coalition, were able to maintain or expand their sovereignty to regulate cross-border finance under global economic governance institutions.
Keywords: 330; Economics; finance; monetary policy; IMF; WTO; Kapitalmobilität; Kapitalverkehrskontrolle; Internationale Wirtschaftsorganisation; G20-Staaten; Wirkungsanalyse; Schwellenländer; Welt